MATHEMATICAL INDUCTION
Suppose we want to prove a mathematical statement
A
(
n
) which is formulated
for every natural number
n
∈
N
, i.e. n=1,2,3,4,.
...
One very often uses the following method (referred to as “mathematical induc
tion”, or simply “induction”) to verify that the statement is true
for all
n
∈
N
.
(i) One proves the statement for
n
= 1
, i.e.
A
(1)
.
(ii) One shows that for every
n
the statement
A
(
n
)
implies the statement
A
(
n
+1)
(in other words, for every
n
it is true that if
A
(
n
)
holds then
A
(
n
+ 1)
holds too).
If we have checked both (i) and (ii) then we know that
A
(2) is true (namely
A
(1)
is true by (i), and therefore, by (ii)
A
(2) is also true). But then
A
(3) is also true
(we have just seen that
A
(2) is true and by (ii) it implies
A
(3)). Etc. etc.
Remark:
The induction does not have to begin with
n
= 1. Suppose we know
that
A
(4) is true and that for all
n
≥
4 the statement “
A
(
n
) implies
A
(
n
+ 1)”
holds then we can conclude that
A
(
n
) is true for all
n
≥
4.
1.
Examples
Example 1.1.
Let’s prove for
n
= 1
,
2
, . . .
the statement
A
(
n
) :
n
X
k
=1
k
=
n
(
n
+ 1)
2
,
In english: the sum of the ﬁrst
n
natural numbers (beginning with 1) is equal to
n
(
n
+1)
2
.
To verify
A
(1) just note that
∑
1
k
=1
= 1 =
1
·
(1+1)
2
.
Now we need to check that for all
n
the truth of
A
(
n
) implies the truth of
A
(
n
+ 1). Fix
n
. We write
n
+1
X
k
=1
k
= (
n
X
k
=1
k
) + (
n
+ 1)
Since we are assuming the truth of
A
(
n
) (for our ﬁxed
n
) we have
∑
n
k
=1
k
=
n
(
n
+1)
2
and we can use this in the last displayed formula. Thus
n
+1
X
k
=1
k
=
n
(
n
+ 1)
2
+ (
n
+ 1) = (
n
+ 1)
±
n
2
+ 1
²
=
(
n
+ 1)(
n
+ 2)
2
and this yields
A
(
n
+ 1).
To summarize we have shown
A
(1) and for all
n
we have shown that
A
(
n
) implies
A
(
n
+ 1). Thus, by mathematical induction it follows that the assertion holds for
all
n
.
±
1
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document2
Example 1.2.
Let’s prove the following statement:
For all
n
∈
N
the inequality
n <
2
n
holds.
We label this statement
A
(
n
).
Clearly
A
(1) holds (namely we have 1
<
2 = 2
1
).
Now let’s ﬁx
n
and show that the validity of
A
(
n
) implies the validity of
A
(
n
+1).
This follows from
n
+ 1
<
2
n
+ 1
<
2
n
+ 2
n
= 2
·
2
n
= 2
n
+1
.
where in the ﬁrst inequality we have used the induction hypothesis (i.e. the assumed
truth of
A
(
n
)) and in the second inequality the obvious statement that 1
<
2
n
for
all
n
= 1
,
2
, . . .
).
By mathematical induction it follows that
This is the end of the preview.
Sign up
to
access the rest of the document.
 Fall '08
 Staff
 Calculus, Linear Algebra, Algebra, Binomial Theorem, Mathematical Induction, Natural number, 1 2 k, 1  k

Click to edit the document details